2015
DOI: 10.1063/1.4919896
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation of nanostructures by surface spinodal decomposition in GaAs1−xBix epilayers

Abstract: We report on the spontaneous formation of lateral composition modulations (LCMs) in Ga(As,Bi) epilayers grown by low-temperature (<300 C) molecular beam epitaxy (MBE) on GaAs(001). Both cross-section and plan-view transmission electron microscopy techniques are used to investigate the nature of the LCMs, consisting of Bi-rich cylinder-like nanostructures lying along the [001] growth direction. The observed LCMs are the consequence of a two-dimensional phase separation process occurring at the surface of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
2
29
1
Order By: Relevance
“…It has been reported that the amplitude of lateral CMs in Ga(As,Bi) is about D[Bi]/[Bi] 30%. 7,8,23 In Ga(As,Bi) with an average Bi content of [Bi] avg ¼ 5%, the presence of a 30% modulation induces a contrast of about 16%, which is readily detectable (we estimate that 3-3.6% contrast is the lower limit of detection that we achieve using g 002 DFTEM 28 ). Assuming that the amplitude of CMs in Ga(Sb,Bi) is as large as that in Ga(As,Bi), a 30% modulation in Ga(Sb,Bi) with [Bi] avg ¼ 14% (or in Ga(Sb,Bi) with [Bi] avg ¼ 11.5% Bi, as a representative composition for the QW samples) would induce a contrast of about 5.7% (5.1%), which is significantly smaller than in Ga(As,Bi) but still detectable.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…It has been reported that the amplitude of lateral CMs in Ga(As,Bi) is about D[Bi]/[Bi] 30%. 7,8,23 In Ga(As,Bi) with an average Bi content of [Bi] avg ¼ 5%, the presence of a 30% modulation induces a contrast of about 16%, which is readily detectable (we estimate that 3-3.6% contrast is the lower limit of detection that we achieve using g 002 DFTEM 28 ). Assuming that the amplitude of CMs in Ga(Sb,Bi) is as large as that in Ga(As,Bi), a 30% modulation in Ga(Sb,Bi) with [Bi] avg ¼ 14% (or in Ga(Sb,Bi) with [Bi] avg ¼ 11.5% Bi, as a representative composition for the QW samples) would induce a contrast of about 5.7% (5.1%), which is significantly smaller than in Ga(As,Bi) but still detectable.…”
mentioning
confidence: 89%
“…4 Among Bi-containing III-V semiconductors, Ga(As,Bi) is the most investigated material, and recent works report morphological instabilities, clustering, and composition modulations (CMs) depending on the specific growth conditions. [5][6][7][8][9] On the contrary, GaSb compounds alloyed with Bi have been far less studied (the first reports on the alloy date back to 2012), 10,11 and questions such as alloy stability, segregation, or solubility limits are still unexplored. In spite of the recent demonstration of laser emission, material developments are still required for the further use of Ga(Sb,Bi) in practical devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent work has shown that good bismuth incorporation can be achieved under wider ranges of V/III ratios when growing with arsenic tetramers (As 4 ). 12 GaAsBi has a tendency to phase separate over a wide range of bismuth fractions (x = 0.02 to 0.13), resulting in films demonstrating strain-influenced lateral compositional modulations, 13 coarse-scale vertical phase separation brought on by droplet formation, 14 or CuPt B -type atomic ordering. 15,16 Phase separation or spinodal decomposition can yield materials with inconsistent optical and electrical properties, 17 as well as introduce defects and trap states that degrade performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, anti-sites, where the group III or V sites have an element from the other site, as has also been seen in GaAs(Bi) [32,33], may increase the observed lattice mismatch. We speculate that it is also possible that in InGaAsBi, bismuth gives rise to inhomogeneities leading to the formation of clusters or other localised structures in the layer similar to that observed in GaAsBi [20,34,35,36]. Additionally, observations of surface roughness from the SEM images ( Fig.…”
Section: Rbs Channelling Measurementsmentioning
confidence: 69%